Role of IL‐6 in dendritic cell functions - Xu, Yu‐Dong; Cheng, Mi; Shang, Pan‐Pan; Yang, Yong‐Qing (Journal of leukocyte biology, 2022)
Dendritic cells (DCs) are efficient antigen‐presenting cells that serve as a link between the innate and adaptive immune systems. These cells are broadly involved in cellular and humoral immune responses by presenting antigens to initiate T cell reactions, cytokine and chemokine secretion, T cell differentiation and expansion, B cell activation and regulation, and the mediation of immune tolerance. The functions of DCs depend on their activation status, which is defined by the stages of maturation, phenotype differentiation, and migration ability, among other factors. IL‐6 is a soluble mediator mainly produced by a variety of immune cells, including DCs, that exerts pleiotropic effects on immune and inflammatory responses through interaction with specific receptors expressed on the surface of target cells. Here, we review the role of IL‐6, when generated in an inflammatory context or as derived from DCs, in modulating the biologic function and activation status of DCs and emphasize the importance of searching for novel strategies to target the IL‐6/IL‐6 signaling pathway as a means to diminish the inflammatory activity of DCs in immune response or to prime the immunogenic activity of DCs in immunosuppressive conditions. Graphical Reviews the role of IL‐6, when generated in an inflammatory context or as derived from dendritic cells (DCs), in modulating the biological function and activation status of DCs.